A Prosódia na expressão de atitudes na fala de indivíduos com e sem gagueira - Leticia Correa Celeste (2010)
A major function of prosody is the expression of attitudes, among them there is the certainty and doubt. Through modulation of parameters such as melodic variation and duration humans are able to transmit to others their communicative intention. However, speech disorders suchas stuttering may have as one of its consequences, difficulties in prosodic organization during the expression of attitudes. This study aimed to analyze the prosody in the expression of attitudes of certainty and doubt in the speech of individuals with and without stuttering.To do so, 24 individuos participated in this research. They were divided in two groups: experimental group (n=12), subdivided in two, one with people with severe stuttering (n=4) and the other with people with moderate stuttering (n=8), and the control group (n=12), withpeople without stuttering. All participants were male, born and resed in Belo Horizonte, with age between 20 and 40 years old. For the recordings, the participants read 10 neutral sentences and the same sentences expressing certainty and doubt. The recordings and theacoustical analisys were done on Praat, version 5.1.02. The prosodic parameters analised were related to the utterance (inicial and final F0, tessitura, F0 peak, pauses, disfluencies, elocution rate and arituclation rate wiht and without disfluencies) and related to the stress and prestress vowels (maximum and minimum F0, pitch and duration).A perceptual test was applied to the utterances of the experimental and control groups, on 60 participants. Statistical analysis included measurements of descriptive statistics and comparison test variables (nonparametric Kruskal Wallis, chi-square test and one-and twoproportions) with a significance of 95%. The results showed statistically significant differences between the experimental and controlgroups. The control group showed more prominent prosodic variation than the experimental expression of attitudes. However, it became clear that the experimental group with moderate stuttering was closer to the control group than the group with severe stuttering. The test results showed that perceptual interlocutors recognize better the attitudes expressed by the control group compared to the experimental.